Hot-water immersion enhances vertical-jump performance, lower-limb power, and stretch-shortening cycle - Rodrigues, P.; Lawley, J. S.; Zovilé, G. C. F.; Jaén-Carrillo, D. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to (a) examine the effects of hot-water immersion (HWI) on vertical-jump performance, lower-limb power, and stretch-shortening cycle responses and (b) evaluate temperature-dependent responses by comparing 2 HWI conditions (40 °C vs 42 °C).